A low-phase-noise 5-GHz CMOS quadrature VCO using superharmonic coupling. - Gierkink, S.L.J (IEEE Journal of solid state circuits)
A new concept for quadrature coupling of LC oscillators is introduced and demonstrated on a 5-GHz CMOS voltage-controlled oscillator (VCO). It uses the second harmonic of the outputs to couple the oscillators. The technique provides quadrature over a wide tuning range without introducing any increase in phase noise or power consumption. The VCO is tunable between 4.57 and 5.21 GHz and has a phase noise lower than -124 dBc/Hz at 1-MHz offset over the entire tuning range. The worst-case measured image rejection is 33 dB. The circuit draws 8.75 mA from a 2.5-V supply.